PENGARUH RASIO SOLVABILITAS, RASIO LIKUIDITAS, DAN RASIO PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN - Muhamad Valdi Jauhari; Indah Ariffianti; Baiq Desthania Prathama (Kredibel: Jurnal Ilmiah Manajemen, 2023)
This study aims to determine the effect of Solvency Ratio, Liquidity Ratio and Profitability Ratio on Stock Price. The financial ratios used to measure this influence are the Debt to Equity Ratio, Current Ratio and Net Profit Margin. This type of research is associative and the sampling technique used is purposive sampling technique. The samples used were 16 Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The analytical method used is multiple linear regression analysis. The results of the multiple linear regression analysis are Y = 1.117 - 0.156 X1 - 0.032 X2 - 0.826 X3. Partially variable solvency ratio (DER) with a significance of 0.078 > 0.05, liquidity ratio (CR) with a significance of 0.142 > 0.05 and profitability ratio (NPM) with a significance of 0.209 > 0.05 showed no significant effect on stock prices. Simultaneously the solvency ratio (DER) variable, liquidity ratio (CR) and profitability ratio (NPM) with a significance of 0.002 <0.05 indicate a significant effect on stock prices